A review of IL-36: an emerging therapeutic target for inflammatory dermatoses. (18th August 2022) - Hwang, Jonwei; Rick, Jonathan; Hsiao, Jennifer; Shi, Vivian Y.
Abstract: Background: IL-36 cytokines are members of the IL-1 superfamily. Increasing evidence in the IL-36 pathway demonstrates their potential as a therapeutic target for treating inflammatory skin diseases, such as generalized pustular psoriasis (GPP). Objective: A narrative review was written to further study preclinical and clinical evidence for the role of IL-36 in psoriasis, atopic dermatitis (AD), hidradenitis suppurativa (HS), acne, autoimmune blistering diseases, and neutrophilic dermatoses. Results: IL-36 has important downstream effects such as inducing expression of inflammatory cytokines, antimicrobial peptides, and growth factors. Increased expression of IL-36 cytokines has been observed in the lesional skin of patients with psoriasis. Studies of other inflammatory skin diseases have also noted similar findings, albeit to a lesser extent. IL-36 inhibition has been shown to be effective in GPP and is currently being studied for other inflammatory skin diseases. Conclusions: The IL-36 pathway contributes to pathogenesis of many inflammatory skin diseases and is a promising therapeutic target.